2019
DOI: 10.3389/fneur.2019.00312
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Gray Matter and Hippocampal Atrophy in Idiopathic Rapid Eye Movement Sleep Behavior Disorder

Abstract: Objective: In this study we investigate cortical and subcortical gray matter structure in patients with Idiopathic REM-sleep behavior disorder (IRBD), and their relation to cognitive performance. Methods: This study includes a sample of 20 patients with polysomnography-confirmed IRBD and 27 healthy controls that underwent neuropsychological and T1-weighted MRI assessment. FreeSurfer was used to estimate cortical thickness, subcortical volumetry (version 5.1), and hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 63 publications
12
37
0
Order By: Relevance
“…As stated in the introduction, there is no previous research investigating brain changes in IRBD over time compared to normal aging. It is interesting noting that already in our cross-sectional study superior parietal thinning was identified in these patients ( Campabadal et al, 2019b ), with our current results, we highlight the involvement of parietal regions in the progression of IRBD. This predominantly posterior cortical pattern is similar to previous findings in PD and DLB ( Delli Pizzi et al, 2014 , Ramírez-Ruiz et al, 2007 , Segura et al, 2014 , Uribe et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As stated in the introduction, there is no previous research investigating brain changes in IRBD over time compared to normal aging. It is interesting noting that already in our cross-sectional study superior parietal thinning was identified in these patients ( Campabadal et al, 2019b ), with our current results, we highlight the involvement of parietal regions in the progression of IRBD. This predominantly posterior cortical pattern is similar to previous findings in PD and DLB ( Delli Pizzi et al, 2014 , Ramírez-Ruiz et al, 2007 , Segura et al, 2014 , Uribe et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Subjects were evaluated at baseline and after 1.6 ± 0.3 years for patients and 1.6 ± 0.2 years for controls of follow-up (U = 127; p = 0.97). All participants are part of a longitudinal cohort recruited between 2015 and 2017 ( Campabadal et al, 2019b ). IRBD patients were recruited from our sleep disorders center and none of them developed parkinsonism during the follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to our knowledge, no study to date has investigated the effect of the early presence of RBD on the pattern of brain atrophy overtime in PD. As a sensitive marker of gray matter atrophy, cortical thinning has been associated with idiopathic RBD 20 , 21 , PD with concomitant RBD 22 , and a risk of conversion to a Lewy body disorder in idiopathic RBD patients 23 . Therefore, in this study, we investigated the association between RBD and changes of cortical thickness and subcortical volumes in early, de novo PD patients from the Parkinson’s Progression Markers Initiative (PPMI) project 24 ( http://www.ppmi-info.org ), cross-sectionally and longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD (Bøen et al, 2014;Chen et al, 2016;Averill et al, 2017;Hayes et al, 2017), childhood maltreatment (Teicher et al, 2012;Chalavi et al, 2015), verbal abuse , childhood trauma in schizophrenia and healthy controls (du Plessis et al, 2019), in bipolar disorders and healthy controls (Janiri et al, 2019a) and in adolescence (Malhi et al, 2019) Other neuropsychiatric conditions Pain symptoms (Ezzati et al, 2014), ADHD (Al-Amin et al, 2018), anorexia nervosa (Myrvang et al, 2018), obsessive compulsive disorder (Zhang et al, 2019), and transient global amnesia (Wang et al, 2018b), essential tremor (Prasad et al, 2019), rapid eye movement sleep behavior disorder (Campabadal et al, 2019), trigeminal neuralgia (Vaculik et al, 2019) Thalamic infarction (Chen et al, 2016), sequelae of microsurgical aneurysm clipping (Hedderich et al, 2019)…”
Section: Posttraumatic Stress Disorder (Ptsd) and Early Life Adversitymentioning
confidence: 99%